Technological Characteristics and Bio-Chemical Composition of Apple Fruit’s (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article describes the results of research on the technological characteristics of apple varieties suitable for drying. In this, the main indicators of apple varieties selected for experiments were analyzed and scientifically based conclusions were made. The article also examines the possibility of preserving fruits grown in agriculture, creating high added value as a result of their processing, and increasing the opportunities for exporting the grown crop not in raw form, but in the form of finished semi-finished products by improving processing technologies. The preservation of the naturalness of apples by drying them, as well as the varieties of dried apples, were studied, the results obtained from drying of all varieties were analyzed on a scientific basis, and proposals and recommendations were developed. Factors such as size and hardness of fruits were analyzed when drying them, and the amount of volume the fruit loses during drying, as well as the expected economic and social effect as a result of the added value in the resulting semi-finished products, were analyzed. The additional jobs created through the introduction of fruit drying technology and the economic efficiency obtained as a result of a sharp reduction in fruit losses were analyzed.